Association between cholelithiasis and sialolithiasis: Two longitudinal follow-up studies - Kim, So Young; Kim, Hyung-Jong; Lim, Hyun; Lim, Man Sup; Kim, Miyoung; Park, Il-Seok; Choi, Hyo Geun (Medicine (Baltimore), 2019)
This study aimed to evaluate the association between cholelithiasis and sialolithiasis using a national sample cohort in Korea.The Korean National Health Insurance Service-National Sample Cohort (patients ≥20 years old) was collected from 2002 to 2013. In study I, we extracted cholelithiasis patients (n = 21,170) and 1:4 matched control I subjects (n = 84,680) and analyzed the occurrence of sialolithiasis. In study II, we extracted sialolithiasis patients (n = 761) and 1:4 matched control II subjects (n = 3044) and analyzed the occurrence of cholelithiasis. Hazard ratios (HRs) were determined using the stratified Cox proportional hazard model.The HR for sialolithiasis was 1.49 (95% CI = 0.88-2.52) in the cholelithiasis group (P = .14), and the HR for cholelithiasis was 1.18 (95% CI = 0.53-2.59) in the sialolithiasis group (P = .69).We did not find an association between cholelithiasis and sialolithiasis.